The cost of managerialism in the university: an autoethnographical account of an academic redundancy process. (1st June 2015) - Joseph, Richard
Abstract : This paper presents an autoethnographical account of the events associated with the author's redundancy from a tenured academic position at Murdoch Business School, Murdoch University, Perth, Western Australia. It is argued that managerialism, a social philosophy that sees the management of a university to be little different from the management of a for-profit business, provided university management with a rationale for a course of action that imposed heavy costs on individuals and undermined core academic values. The apparent weakness of the protection provided by tenure is highlighted by the mechanisms through which university management exerted control over the academic employment relationship. The cost of imposing management's will to win at all costs corrodes valuable aspects of academic work, such as collegiality, trust and the sharing of information. The paper shows that the various mechanisms of control imposed by a university management that adheres to managerialist principles can destroy much of what is worthwhile in the university. What is left is something with little spirit and nothing worthwhile to manage.